Participação convencional e nao convencional na América Latina - Borba, Julian; Ribeiro, Ednaldo Aparecido (Revista Latinoamericana de Opinión Pública, 2010)
This article deals with the relationships between conventional and non-conventional forms of participation. The data were extracted from a survey conducted in three South American capitals (Porto Alegre, Montevideo and Santiago). Using multivariate analysis techniques, the relations between socio-demographical, attitudinal and behavioral variables were tested within the distinct forms of participation. In the three cities, participation in one of the modalities (conventional or non-conventional) was found to be the main predictor of participation in the other, a fact that serves as empirical validation for the theories of participation that view political engagement as a product of the context and repertoires that are mobilized by the social actors.